2022
DOI: 10.21203/rs.3.rs-1677219/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of an Artificial Intelligence-assisted Antibiotic Susceptibility Test on Reducing the Mortality Rate of and Antibiotics Use in Patients with Bacteremia: A Prospective Observational Cohort Study

Abstract: No mass spectrometry-based antibiotic susceptibility test (AST) AI system has been robustly validated and truly deployed in real-world settings. In the study, an AI-assisted AST prediction system XBugHunter was extensively validated and deployed. A total of 90,064 consecutive patients were included in the models development. During the deployment, 155 consecutive patients with Staphylococcus aureus bacteremia (SAB) was analyzed, whereas the historical control cohort included 455 patients. The predictive sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…At the same time, the AUROC of the ML model attained 0.89 [33]. In another large-scale research of ESKAPE pathogens, all the t-SNE plots of MALDI-TOF spectra showed no specific pattern for discriminating resistant pathogens from susceptible ones [22]. Likewise, the predictive performance attained as high as 0.95 for detecting oxacillin resistance for Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…At the same time, the AUROC of the ML model attained 0.89 [33]. In another large-scale research of ESKAPE pathogens, all the t-SNE plots of MALDI-TOF spectra showed no specific pattern for discriminating resistant pathogens from susceptible ones [22]. Likewise, the predictive performance attained as high as 0.95 for detecting oxacillin resistance for Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 94%
“…The peak is suspected to be in accordance with the peak of m/z 9478 that was found in our study (Figure 9B). The subtle difference between m/z 9473 and 9478 resulted from shifting problem caused by isotopes, so m/z 9473 and 9478 could be regarded as the same peptide molecules [22,37]. Based on previous studies, peak of m/z 9478 occurred less than 40% in either subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation